1986
DOI: 10.1159/000146180
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Pulmonary Vascular Endothelium in Rats with Hypoxia-Induced Hypertension

Abstract: Scanning electron microscopy was used to study the endothelial surface of the pulmonary trunk, artery, and vein in normobaric control rats as well as in rats exposed to hypobaric hypoxia for 7 and 21 days. The individual endothelial cells of the normobaric pulmonary trunk and hilar artery were flat and slightly elongated with elevated nuclear regions, and those of the intermediate-sized artery were more elongated and had more microvilli than the large arteries studied. Their endothelial cell boundaries were ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Control endothelium examined by SEM resembled that reported previously. 6 The crater-like cytoplasmic defects produced by ETX have also been described in these cells in vitro under conditions of hypertension, ischemia, and hypoxia, 5 and after exposure to the neurotoxin, tunicamycin. 1…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Control endothelium examined by SEM resembled that reported previously. 6 The crater-like cytoplasmic defects produced by ETX have also been described in these cells in vitro under conditions of hypertension, ischemia, and hypoxia, 5 and after exposure to the neurotoxin, tunicamycin. 1…”
Section: Discussionmentioning
confidence: 96%
“…Control endothelium examined by SEM resembled that reported previously. 6 The crater-like cytoplasmic defects produced by ETX have also been described in these cells in vitro under conditions of hypertension, ischemia, and hypoxia, 5 and after exposure to the neurotoxin, tunicamycin. 1 Although the endothelial cell line that we used was of human origin, we nevertheless demonstrated that ETX is capable of injuring brain endothelium directly in vitro and it is likely that it would similarly damage cultured cerebral endothelial cells from species known to be susceptible to EXT neurotoxicity, such as ruminant livestock, particularly sheep, and laboratory rodents.…”
Section: Discussionmentioning
confidence: 96%
“…The question is whether the processes of hypertrophy and recovery are symmetric. Considerable data on the building up of the lung tissue due to pulmonary hypertension have been obtained (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Some data on recovery from hypertension are also given in refs.…”
mentioning
confidence: 99%
“…As a specific illustration, we consider the changes that occur in the lung when a sea-level dwelling animal is flown to a ski resort at a higher altitude where the partial pressure of oxygen in the gas that the animal breathes is lower. What happens is that the pulmonary arterial blood pressure becomes higher (1-3), the arterial blood vessel wall becomes thicker (3)(4)(5), the different layers of the arteries thicken with different rates and different courses of time (2)(3)(4)(5)(6), the mechanical properties of the blood vessel wall change with specific historical courses (7)(8)(9), cells in the wall modify, grow, proliferate, or move (5,6,(10)(11)(12)(13), intercellular matrix and interstitial space change (14,15), the stress and strain distribution in the vessel wall change with time in a specific way (16), and because of cellular and extracellular changes the zero-stress state of the blood vessel wall changes with time (7)(8)(9). The crucial fact is the blood pressure change, because the blood pressure imposes load on the blood vessel wall, causing stress and strain, and the subsequent tissue and mechanical properties remodeling are believed to be the results of these stress and strain changes.…”
mentioning
confidence: 99%